Customizing Heterointerfaces in Multilevel Hollow Architecture Constructed by Magnetic Spindle Arrays Using the Polymerizing‐Etching Strategy for Boosting Microwave Absorption. Issue 17 (11th April 2022) - Xu, Chunyang; Liu, Panbo; Wu, Zhengchen; Zhang, Huibin; Zhang, Ruixuan; Zhang, Chang; Wang, Lei; Wang, Longyuan; Yang, Bingtong; Yang, Ziqi; You, Wenbin; Che, Renchao
Abstract: Heterointerface engineering is evolving as an effective approach to tune electromagnetic functional materials, but the mechanisms of heterointerfaces on microwave absorption (MA) remain unclear. In this work, abundant electromagnetic heterointerfaces are customized in multilevel hollow architecture via a one‐step synergistic polymerizing‐etching strategy. Fe/Fe3 O4 @C spindle‐on‐tube structures are transformed from FeOOH@polydopamine precursors by a controllable reduction process. The impressive electromagnetic heterostructures are realized on the Fe/Fe3 O4 @C hollow spindle arrays and induce strong interfacial polarization. The highly dispersive Fe/Fe3 O4 nanoparticles within spindles build multi‐dimension magnetic networks, which enhance the interaction with incident microwaves and reinforce magnetic loss capacity. Moreover, the hierarchically hollow structure and electromagnetic synergistic components are conducive to the impedance matching between absorbing materials and air medium. Furthermore, the mechanisms of electromagnetic heterointerfaces on the MA are systematically investigated. Accordingly, the as‐prepared hierarchical Fe/Fe3 O4 @C microtubes exhibit remarkable MA performance with a maximum refection loss of −55.4 dB and an absorption bandwidth of 4.2 GHz. Therefore, in this study, the authors not only demonstrate a synergistic strategy to design multilevel hollow architecture, but also provide a fundamental guide in heterointerface engineering of highly efficient electromagnetic functional materials. Abstract : A hierarchical multilevel hollow architecture of Fe/Fe3 O4 @C microtubes are developed for the first time via a one‐step polymerizing‐etching strategy. The Fe/Fe3 O4 @C composites are assembled by hollow spindle arrays and the inner microtube, constructing abundant electromagnetic heterointerfaces and achieving spatially dispersed magnetic nanoparticles, which exhibits strong polarization loss and multi‐scale magnetic loss.